2022
DOI: 10.3389/fncel.2021.819194
|View full text |Cite
|
Sign up to set email alerts
|

Connexin30-Deficiency Causes Mild Hearing Loss With the Reduction of Endocochlear Potential and ATP Release

Abstract: GJB2 and GJB6 are adjacent genes encoding connexin 26 (Cx26) and connexin 30 (Cx30), respectively, with overlapping expressions in the inner ear. Both genes are associated with the commonest monogenic hearing disorder, recessive isolated deafness DFNB1. Cx26 plays an important role in auditory development, while the role of Cx30 in hearing remains controversial. Previous studies found that Cx30 knockout mice had severe hearing loss along with a 90% reduction in Cx26, while another Cx30 knockout mouse model sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Our hypothesis is that the increase of oxidative stress and cochlear redox imbalance caused by connexin downregulation can, in turn, cause stria vascularis dysfunction and vascular dysregulation, worsening cochlear-aging processes. Moreover, our results are consistent with the literature findings showing alterations in cochlear blood flow and extravasation in Cx30 KO animal models (Cohen-Salmon et al, 2007) and a crucial role of Cx30 in maintaining the endocochlear potential (Chen et al, 2022). Considering that cochlear vascular changes, vasoconstriction, or alterations in cochlear blood flow are well known risk factors for ARHL (Lyu et al, 2020;Peixoto Pinheiro et al, 2021), it is plausible that total deletion of Cx30, in conjunction with Cx26 downregulation, can increase cochlear susceptibility to vascular damage, exacerbating aging processes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our hypothesis is that the increase of oxidative stress and cochlear redox imbalance caused by connexin downregulation can, in turn, cause stria vascularis dysfunction and vascular dysregulation, worsening cochlear-aging processes. Moreover, our results are consistent with the literature findings showing alterations in cochlear blood flow and extravasation in Cx30 KO animal models (Cohen-Salmon et al, 2007) and a crucial role of Cx30 in maintaining the endocochlear potential (Chen et al, 2022). Considering that cochlear vascular changes, vasoconstriction, or alterations in cochlear blood flow are well known risk factors for ARHL (Lyu et al, 2020;Peixoto Pinheiro et al, 2021), it is plausible that total deletion of Cx30, in conjunction with Cx26 downregulation, can increase cochlear susceptibility to vascular damage, exacerbating aging processes.…”
Section: Discussionsupporting
confidence: 93%
“…Looking for a molecular mechanism, we focused on the crossroad among oxidative stress, inflammation, and vascular dysfunction, considering that these damaging factors are common pathological markers of aging processes both in physiological cochlear-aging and in the genetic model of ARHL ( Someya et al, 2009 ; Fetoni et al, 2018 ; White et al, 2018 ; Wang and Puel, 2020 ; Fetoni et al, 2022 ). Moreover, at the same time, deletions of connexins have been related to oxidative-inflammatory processes ( Fetoni et al, 2018 ; Hua et al, 2021 ), as well as to vascular dysfunction and reduced endocochlear potential ( Cohen-Salmon et al, 2007 ; Gentile et al, 2021 ; Chen et al, 2022 ). Our data, demonstrating that the absence of Cx30 and the consequent downregulation of Cx26 are associated with increased ROS amount in Cx30 ΔΔ aged-cochleae, suggest that connexin hemichannels play a key role in protecting against oxidative stress during aging, probably allowing diffusion of antioxidant molecules to counteract redox imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is like the phenotype of DFNA3 or DFNB1. The common pathophysiological alterations of these model mice are the active cochlear amplification impairment which showed that distortion product otoacoustic emission (DPOAE) failed to evoke at an early stage ( Chen et al, 2021 ). With aging, hair cells at the basal turn first start to damage and then gradually expand to the middle and apic turns ( Fetoni et al, 2018 ).…”
Section: Mouse Models Of Connexin 26 Deficiencymentioning
confidence: 99%
“…Potassium recycling is such a process that potassium flows through ion channels in the cochlear GJ system from the perilymph into the endolymph, participating in the formation of hair cell receptor potentials and stable endocochlear potential (EP), finally returning to the perilymph ( Lv et al, 2021 ; Figure 1 ). Potassium recycling is thought to be critical for maintaining high endolymphatic potassium concentrations and EP ( Chen et al, 2021 ).…”
Section: Pathological Mechanisms Of Connexin26-related Hearing Lossmentioning
confidence: 99%